Patient-Reported Health Outcomes and Quality of Life after Peripartum Hysterectomy for Placenta Accreta Spectrum - Grover, Bryan; Einerson, Brett D.; Keenan, Karissa D.; Gibbins, Karen J.; Callaway, Emily; Lopez, Sarah; Silver, Robert M. (American Journal of Perinatology, 2020)
Objective Short-term morbidity of placenta accreta spectrum (PAS) is well described, but few data are available regarding long-term outcomes and quality of life. We aimed to evaluate patient-reported outcomes after hysterectomy for PAS.Study Design This is a prospective cohort study of women with risk factors for PAS who were enrolled antenatally. Exposed women were defined as those who underwent cesarean hysterectomy due to PAS. Unexposed women were those with three or more prior cesareans or placenta previa, but no PAS, who underwent cesarean delivery without hysterectomy. Two surveys were sent to patients at 6, 12, 24, and 36 months postpartum: (1) a general health questionnaire and (2) the SF-36, a validated quality of life survey. Aggregate scores for each questionnaire were calculated and responses were analyzed.Results At 6 months postpartum, women with PAS were more likely to report rehospitalization (odds ratio [OR] 5.83, 95% confidence interval [CI] 1.40–24.3), painful intercourse (OR 2.50, 95% CI 1.04–6.02), and anxiety/worry (OR 3.77, 95% CI 1.43–9.93), but were not statistically more likely to report additional surgeries (OR 3.39, 95% CI 0.99–11.7) or grief and depression (OR 2.45, 95% CI 0.87–6.95). At 12 months, women with PAS were more likely to report painful intercourse, grief/depression, and anxiety/worry. At 36 months, women with PAS were more likely to report grief/depression, anxiety/worry, and additional surgeries. Women with PAS reported significantly lower quality of life in physical functioning, role functioning, social functioning, and pain at 6 months postpartum, but not in other quality of life domains. Decreased quality of life was also reported at 12 and 36 months in the PAS group.Conclusion Women with PAS are more likely to report ongoing long-term health issues and decreased quality of life for up to 3 years following surgery than those undergoing cesarean for other indications.Key Points
Keywords: placenta accreta spectrum; quality of life; mental health; birth trauma; cesarean